Stem Cells Within Three-Dimensional-Printed Scaffolds Facilitate Airway Mucosa and Bone Regeneration and Reconstruction of Maxillary Defects in Rabbits - Mi Hyun Lim; Jung Ho Jeon; Sun Hwa Park; Byeong Gon Yun; Seok-Won Kim; Dong-Woo Cho; Jeong Hak Lee; Do Hyun Kim; Sung Won Kim (Medicina)
Background and Objectives: Current craniofacial reconstruction surgical methods have limitations because they involve facial deformation. The craniofacial region includes many areas where the mucosa, exposed to air, is closely adjacent to bone, with the maxilla being a prominent example of this structure. Therefore, this study explored whether human neural-crest-derived stem cells (hNTSCs) aid bone and airway mucosal regeneration during craniofacial reconstruction using a rabbit model. Materials and Methods: hNTSCs were induced to differentiate into either mucosal epithelial or osteogenic cells in vitro. hNTSCs were seeded into polycaprolactone scaffold (three-dimensionally printed) that were implanted into rabbits with maxillary defects. Four weeks later, tissue regeneration was analyzed via histological evaluation and immunofluorescence staining. Results: In vitro, hNTSCs differentiated into both mucosal epithelial and osteogenic cells. hNTSC differentiation into respiratory epithelial cells was confirmed by Alcian Blue staining, cilia in SEM, and increased expression levels of FOXJ1 and E-cadherin through quantitative RT-PCR. hNTSC differentiation into bone was confirmed by Alizarin Red staining, increased mRNA expression levels of BMP2 (6.1-fold) and RUNX2 (2.3-fold) in the hNTSC group compared to the control. Four weeks post-transplantation, the rabbit maxilla was harvested, and H&E, SEM, and immunohistofluorescence staining were performed. H&E staining and SEM showed that new tissue and cilia around the maxillary defect were more prominent in the hNTSC group. Also, the hNTSCs group showed positive immunohistofluorescence staining for acetylated α-tubulin and cytokerin-5 compared to the control group. Conclusions: hNTSCs combined with PCL scaffold enhanced the regeneration of mucosal tissue and bone in vitro and promoted mucosal tissue regeneration in the in vivo rabbit model.